2011
DOI: 10.1590/s0104-11692011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Social representations of AIDS and their quotidian interfaces for people living with HIV

Abstract: Representaciones sociales del SIDA para personas que viven con HIV y sus interfaces cotidianasSe trata de un estudio cualitativo descriptivo orientado por la Teoría de las Representaciones Sociales, que objetivó describir el contenido de las representaciones sociales acerca de la Síndrome de Inmunodeficiencia Adquirida (SIDA) para los usuarios seropositivos en acompañamiento de ambulatorio en la red pública de salud y analizar la interconexión de las representaciones sociales del Sida con lo cotidiano de los i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
46

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 8 publications
2
31
0
46
Order By: Relevance
“…All of these factors directly influence the quality of life of HIV-infected people and their families and, most of the time, affecting treatment. (21) We observed that parity, represented in our study by the number of children having been born, tended to be associated with ability level of administrating TMP-SMZ. Some studies that evaluated families of HIV/AIDS-positive people showed that families with more children have a higher risk of nonadherence to antiretroviral therapy or to other medicines.…”
Section: Discussionsupporting
confidence: 47%
“…All of these factors directly influence the quality of life of HIV-infected people and their families and, most of the time, affecting treatment. (21) We observed that parity, represented in our study by the number of children having been born, tended to be associated with ability level of administrating TMP-SMZ. Some studies that evaluated families of HIV/AIDS-positive people showed that families with more children have a higher risk of nonadherence to antiretroviral therapy or to other medicines.…”
Section: Discussionsupporting
confidence: 47%
“…The low level of knowledge about sexuality of the elderly demonstrated by the participants of this study highlights the need for new actions and programs to prevent HIV/AIDS as, although the incidence of the disease is increasing among the elderly, they normally do not see themselves as a risk group (28) . In Brazil, transformations have been recorded on the epidemiological profile of people with HIV/AIDS, being the most significants the feminization, the heterosexualization, the interiorization, the ageing, the low education and the pauperization (29) . In this study the population consisted of 67% white, 9% black, 23% mixed and 1% Asian.…”
Section: Discussionmentioning
confidence: 99%
“…En Brasil, la epidemia surgió en el inicio de la década de 1980, estando asociada a los homo/bisexuales masculinos, usuarios de drogas inyectables y profesionales del sexo (2) . La supuesta selectividad de determinados grupos a la infección suscitó el uso de la terminología "grupo de riesgo", de modo que esta denominación marcó la construcción histórica y social del Síndrome de la Inmunodeficiencia Adquirida (SIDA), popularmente conocida por su sigla derivada del inglés, AIDS (3) . La denominación de grupos de riesgo, para englobar los grupos poblacionales más acometidos por la infección, provocó una respuesta social, caracterizada por estigma y discriminación, asociando este grupo a transgresores de normas sociales como promiscuos, inmorales y viciosos.…”
Section: Introductionunclassified